2021
DOI: 10.3389/fgene.2021.740794
|View full text |Cite
|
Sign up to set email alerts
|

CBX7 is Dualistic in Cancer Progression Based on its Function and Molecular Interactions

Abstract: Chromobox protein homolog 7 (CBX7) is a member of the Chromobox protein family and participates in the formation of the polycomb repressive complex 1(PRC1). In cells, CBX7 often acts as an epigenetic regulator to regulate gene expression. However, pathologically, abnormal expression of CBX7 can lead to an imbalance of gene expression, which is closely related to the occurrence and progression of cancers. In cancers, CBX7 plays a dual role; On the one hand, it contributes to cancer progression in some cancers b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 84 publications
0
7
0
1
Order By: Relevance
“…Interestingly, a recent study revealed a distinct role of two isoforms of CBX7 (p36 CBX7 and p22 CBX7 ) in cell proliferation [39]. In particular, p22 CBX7 potentially interacts with cell cycle regulators [40]. We found that low expression of CBX7 increases genome instability, suggesting that its loss may lead to misregulation of the cell cycle and subsequently cause chromosomal instability.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, a recent study revealed a distinct role of two isoforms of CBX7 (p36 CBX7 and p22 CBX7 ) in cell proliferation [39]. In particular, p22 CBX7 potentially interacts with cell cycle regulators [40]. We found that low expression of CBX7 increases genome instability, suggesting that its loss may lead to misregulation of the cell cycle and subsequently cause chromosomal instability.…”
Section: Discussionmentioning
confidence: 61%
“…The Wnt signaling pathway has been shown to be critical for IEC proliferation and renewal of intestinal epithelial stem cells, and mutations in this pathway are strongly associated with colon cancer. Importantly, among the 35 significantly upregulated miR-181 –predicted targets in DKO IECs during DSS-induced colitis, we also found five additional putative inhibitors of the Wnt signaling pathway ( Cbx7 , Sox6 , Nr1h4 , Setd7 , and Dgkq ; Kim et al, 2015 ; Li et al, 2021 ; Pei et al, 2020 ; Leow et al, 2016 ; Yu et al, 2020 ; Shen et al, 2015 ; Jacob et al, 2011 ). While upregulation of some miR-181 –predicted targets can be the consequence of enhanced colon inflammation, these results also suggest that the miR-181 family could directly promote the activation of the Wnt signaling pathway during DSS-induced colitis to enhance IEC proliferation and repair.…”
Section: Resultsmentioning
confidence: 75%
“…The role of CBX7 expression in tumours is not clear. It has been linked to inhibition of primary tumour progression in vivo once tumours were already established, but also plays an oncogenic role in some cancers [ 51 , 52 ]. Thus, we examined whether increased stable expression of CBX7 by rAAV with piggyBac transposase-mediated somatic integration in established primary WT tumour cells could inhibit tumour progression in vivo.…”
Section: Resultsmentioning
confidence: 99%